Interaction of cyclic thiadiynes with CpCo(COD): selectivity and reactivity - Gleiter, Rolf; Claßen, Jörg; Rausch, Bernhard J.; Oeser, Thomas; Rominger, Frank (Journal of organometallic chemistry, 2002)
The reaction of CpCo(COD) with several cyclic thiadiynes leads to selective product formation; according to their ring size either (2,5)[2.2]thiophenophanes or CpCo-stabilized cyclobutadienes were formed. The outcome of the reaction can be attributed to the geometry in the transition states, 6 and 11. X-ray structure analyses of the reacting thiacycles and the isolated CpCo compounds are given and correlated with the tautness of the cobaltols.
Available online 14 December 2001
Dedicated to Professor Marianne Baudler on the occasion of her 80th birthday
Gesehen am 28.10.2020
Keywords: Festschrift